Analisa Uji Model Fisik Pelimpah Bendungan Sukahurip Di Kabupaten Pangandaran Jawa Barat - Lufira, Rahmah Dara; Marsudi, Suwanto (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
Pangandaran regency is located on West Java. Sukahurip Dam will be built to fulfill community needs of raw water supply. To solve this problem, the government is planning the construction of dams. Hydrauic analysis of physical models Sukahurip Dam spillway is one of the procedures to planning the dam. The purpose of the analysis of physical models Sukahurip Dam is researching and provide the best planning alternative for the performance improvement of hydraulics spillway based on the original design. Hydraulic analysis of physical models is based on original design. The final result of physical model is indicates that the design of the dam was safe but for the safety of scouring should be groundsill added on the downstream of stilling basin.Key words: Dams, Spillway, Scouring, Models test, Hydraulic